Expert perspectives on incorporating justice considerations into integrated assessment modelling - Sean Low; Elina Brutschin; Chad M. Baum; Benjamin K. Sovacool (npj Climate Action)
Abstract There is growing criticism aimed towards global integrated assessment models (IAMs) and an ongoing academic debate on how justice considerations can be incorporated in those models. By relying on 39 interviews with a multidisciplinary group of experts, we map three shapes of change containing multiple avenues for incorporating justice considerations into IAM tools and scenarios: to improve representation within IAMs (Shape 1), to couple to new models and expand points of access to disciplines and users (Shape 2), and to refine the role of IAMs within a wider array of practices (Shape 3). These shapes reflect multi-disciplinary agreements and divergences over the capacity of IAMs to incorporate justice considerations—regarding kinds of representation, greater involvement of new disciplines and users, and the objective of mitigation scenarios in climate policy. Our analysis is among the first to describe and integrate a variety of opinions from different communities, fostering a more holistic understanding of the opportunities and challenges of incorporating justice into IAMs.